Caósmica valuation of the globalization in the educational systems: a critical approach from decolonial philosophy - Huanca-Arohuanca, Jesús; Sucari, Wilson; Moriano, José; Sapana-Valdivia, Nancy (Revista Innova Educación, 2019)
This article reflects on the contradictions of the caósmica valoration of globalization in the educational systems intoned and seen from the decolonial philosophy. Being the research, of bibliographic documentary type and theoretical-conceptual review, based on the interpretation that gives the qualitative methodological orientation. In that vein, the results reveal the focus of the civilizing resistance on the education of emerging underworlds, based on the approach to the importance of critical humanizing teaching, focusing on the reality of students with canons responding to educational prognosis, but that generate rational and efficient contradictions against those that manage globalization. In conclusion, an education based on a decolonial model that is not only dedicated to instructing but teaching critical thinking, it turns out to be in the end a danger for the system - world capitaloceno, danger to be born with this pronouncement from those who teach, receive the teaching and from those who do not yet know that they will join the project of the educational act with a censor sense.